Improving the “Leader–Follower” Relationship: Top Manager or Supervisor? The Ethical Leadership Trickle-Down Effect on Follower Job Response - Ruiz, Pablo; Ruiz, Carmen; Martínez, Ricardo (2011)
Since time immemorial, the phenomenon of leadership and its understanding has attracted the attention of the business world because of its important role in human groups. Nevertheless, for years efforts to understand this concept have only been centred on people in leadership roles, thus overlooking an important aspect in its understanding: the necessary moral dimension which is implicit in the relationship between leader and follower. As an illustrative example of the importance of considering good morality in leadership, an empirical study is conducted in which a good performance of the “leader–follower” relationship is reflected when individuals perceive ethical leadership in higher hierarchical managerial levels. To be precise, findings of this study demonstrate that follower job response is improved through an ethics trickle-down partial effect from the Top Manager to the immediate supervisor, and also reveal both key aspects and managerial level on which the practice of ethical leadership should rest upon to have a stronger effect on the follower positive job response. Practical implications of these findings and directions for future research are finally presented.
Keywords: trickle-down effect; “leader–follower” relationship; Leadership; job response; Ethics